A Phase I/II Study of a 72-h Continuous Infusion of Etoposide in Advanced Soft Tissue Sarcoma. (1997) - Crawley, Charles R.; Judson, Ian R.; Verrill, Mark; Hill, Catherine; Raynaud, Florence I.
Abstract : Purpose . The study was performed to assess the antitumour activity and toxicity of a 72-h continuous infusion of single-agent etoposide as second-line treatment for patients with locally advanced or metastatic soft tissue sarcoma (STS), following reports of substantial activity using this schedule of etoposide administration as first-line treatment in combination with ifosfamide. Patients/method . This was an open phase I/II trial performed at a single institution in patients with metastatic or locally advanced STS who had failed first-line treatment with doxorubicin + ifosfamide combination chemotherapy or, less commonly, single-agent treatment with doxorubicin or ifosfamide. Etoposide was given as a continuous intravenous infusion over 72 h. The starting dose level was 200 mgm − 2 day − 1 × 3 escalating in 10% steps in cohorts of three patients until dose-limiting toxicity was encountered. Results . Seventeen patients were treated, median age 47 years (range 26–71 years). No responses were seen in 16 assessable patients despite etoposide levels in the cotoxic range. The steady-state plasma concentration exceeded 8 μ g ml − 1 in all patients and in patients treated at ≥ 600 mg m − 2 the mean steady-state level was 14.4 μ g ml − 1 . The median event-free survival was 6 weeks (95% confidence interval (CI) 3.31–8.69) and the overall survival 16 weeks (95% CI 9.28–22.72). The maximum tolerated dose in this pretreated patient group was 200 mg m − 2 day − 1 × 3. The dose-limiting toxicity was myelosuppression. Discussion . Etoposide given by 72-h infusion is inactive as second-line chemotherapy in STS. It is associated with significant toxicity when given in these doses, in this patient group.